(untitled) (Research, Society and Development, 2022)
Introduction. Cycling is a sport that comes with many supporters. However, this increase is accompanied by an increase in the consumption of food supplements; stimulated mainly by the gain of energy and muscular hypertrophy, impacting in a positive way in the evolution of the practical performance. However, the use cannot be done arbitrarily, professional monitoring is necessary to avoid misuse and intoxication by various substances. Objective. Presence of the use of dietary supplements for cyclists in conjunction with the monitoring of specialized professionals to be identified. Methodology. This is an observational, transversal problem, developed in cities in the interior of Goiás, with a study of an open and semi-structured state, using the Google application digital form tool, there were 57 cyclists. The research was approved and authorized by the Research Ethics Committee (CEP). Results. It was found that of the 57 cyclists, 54.4% consume food supplements. Of those who used, 40.4% were recommended by nutritionists; 36.8% by referral from friends and/or colleagues; 17.5% by physical educator and/or personal trainer; 12.3% were influenced by advertising/internet ads; 5.3% by medical advice; 1.8% by pharmacists; another 1.8% by referral from sellers. Conclusion. The use of dietary supplements is a strategy used by most cyclists. The search for guidance and monitoring of use, by qualified professionals, was found, however, the fact that some do not follow or seek or seek guidance is worrying, in view of the indiscriminate use, with risk of harm to the practice.